2021
DOI: 10.32457/ijmss.v8i3.1634
|View full text |Cite
|
Sign up to set email alerts
|

Description of the characteristics of the clinical incidents reported in 2020 to the voluntary reporting system of a pediatric hospital in Costa Rica

Abstract: The objective of this manuscript was to describe the clinical incidents that were sent to the voluntary reporting system during 2020 at the National Children's Hospital of Costa Rica, belonging to the Costa Rican Social Security Fund. A descriptive observational study of the consolidated data that was sent during the months of January to December of the year 2020 was carried out. During 2020, 1.6% of the patients treated in the hospital experienced some type of clinical incident. The total discharges decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
4

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 6 publications
1
3
0
4
Order By: Relevance
“…The data from this research are similar to the results found in other studies that address the characteristics of safety incidents before and also during the COVID-19 period (9,(12)(13)(14) . It is worth noting that institution A had more than triple the number of incident records (n=105) compared to institution B (n=32), a fact that may be related to the greater encouragement and proposal of strategies for notification in the institution A, for the continuous development of a safety culture and for having an international certification process by the Joint Commission International.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The data from this research are similar to the results found in other studies that address the characteristics of safety incidents before and also during the COVID-19 period (9,(12)(13)(14) . It is worth noting that institution A had more than triple the number of incident records (n=105) compared to institution B (n=32), a fact that may be related to the greater encouragement and proposal of strategies for notification in the institution A, for the continuous development of a safety culture and for having an international certification process by the Joint Commission International.…”
Section: Discussionsupporting
confidence: 88%
“…However, some research differs as to which gender is most affected. A study conducted during the pandemic shows that 60.2% of incidents affected children between 29 days and 5 years old, with these incidents occurring predominantly in males (66%) (13) . The IU (n=66; 48.2%), ICU (n=38; 27.7%) and surgical center (n=11; 8.0%) represented the places with the highest prevalence of AEs in this research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Os dados desta pesquisa são similares aos resultados encontrados em outros estudos que abordam as características dos incidentes de segurança antes e também durante o período da COVID-19 (9,(12)(13)(14) . Cabe ressaltar que, a instituição A teve mais do que o triplo de registros de incidentes (n=105) em comparação a instituição B (n=32), fato que pode ser relacionado ao maior incentivo e proposição de estratégias para a notificação na instituição A, pelo desenvolvimento contínuo de uma cultura de segurança e por ter um processo de certificação internacional pela Joint Commission International.…”
Section: Discussionunclassified